Analisis Yuridis Terhadap Kekuatan Hukum Perjanjian Kredit Tanpa Jaminan Dalam Putusan Nomor 360/PDT.G/2017/PN.Jkt.Sel. - Dewi Sulistianingsih; Farras Eknu Albin; Risqi Budi; Christian Bagas; Rois Faisal; Danis Danendra Adhi (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
ABSTRACT This research is motivated by the legal risks of providing unsecured credit, which impact the uncertainty of fulfilling creditors' rights. The purpose of this study is to analyze the legal force of unsecured credit agreements under Decision Number 238/PDT/2018/PT.DKI, the forms of legal protection for creditors in the event of default, and the implications of the lack of material collateral on the creditor's position. The research method used is normative juridical with a statute approach and a case approach. The results show that unsecured credit agreements remain legally binding on the parties under Articles 1320 and 1338 of the Civil Code (pacta sunt servanda). Decision Number 238/PDT/2018/PT.DKI confirms that the lack of material collateral does not eliminate the debtor's obligation to repay the debt. However, in practice, the creditor loses preferential rights and remains only a concurrent creditor. Legal protection for creditors in this case is limited to general collateral as stipulated in Article 1131 of the Civil Code, which requires creditors to share proportionally with other creditors all of the debtor's assets. The conclusion of this study is that although the agreement remains valid, the absence of specific collateral significantly weakens the creditor's bargaining position and legal certainty in obtaining repayment of receivables in the event of default. Keywords: Credit Agreement; Unsecured Credit; Legal Protection; Concurrent Creditors.